The teacher's funeral : [compact disc, unabridged] : a comedy in three parts - Peck, Richard, 1934-2018 (Random House/Listening Library, 2004)
In rural Indiana in 1904, fifteen-year-old Russell's dreams of quitting school and joining a wheat threshing crew are disrupted when his older sister takes over the teaching at his one-room schoolhouse after mean old Myrt Arbuckle "hauls off and dies."